The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1111/j.1476-5381.1976.tb07478.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis of Enzyme Systems Deaminating Different Monoamines

Abstract: I A detailed investigation into the postnatal development of the activity of the enzyme monoamine oxidase (MAO) in the rat and domestic pig was carried out. 2 MAO activity was measured in littermate male rats aged between 3 and 122 days belonging to six breeding colonies. The tissues studied were three brain regions in which monoamines may play a role in neuronal transmission (septum, hypothalamus, corpus striatum) and, for comparison, in the cerebellum. Liver, heart and adrenal glands were the peripheral orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…This completely independent development of MAO deaminating 5-HT and PEA confirms the existence of A and B forms of MAO in lung. The observation that in lung, MAO activity metabolizing PEA increased up to 80 days is in contrast to results in most other organs, but agrees with MAO activity in rat heart which did not reach maximum values by the end of the 4th month of development (Blatchford et al, 1976). These results also suggest that in lung, dopamine is a substrate for MAO-B in younger animals up to 20 days old and becomes a substrate also for MAO-A in older animals.…”
Section: Uptake In Perfused Lungsupporting
confidence: 78%
See 2 more Smart Citations
“…This completely independent development of MAO deaminating 5-HT and PEA confirms the existence of A and B forms of MAO in lung. The observation that in lung, MAO activity metabolizing PEA increased up to 80 days is in contrast to results in most other organs, but agrees with MAO activity in rat heart which did not reach maximum values by the end of the 4th month of development (Blatchford et al, 1976). These results also suggest that in lung, dopamine is a substrate for MAO-B in younger animals up to 20 days old and becomes a substrate also for MAO-A in older animals.…”
Section: Uptake In Perfused Lungsupporting
confidence: 78%
“…BJP 72:4 J Discussion Age-dependent changes in uptake of amines (Kirksey & Slotkin, 1980) and in MAO activity (Blatchford et al, 1976) in various tissues of the rat have been reported. Our results have shown that in lung, uptake and MAO activity also changed with age and thus lung responds like other tissues.…”
Section: Uptake In Perfused Lungmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the rates of recovery of the two forms after inhibi tion by pargyline were found to be similar [5]. The data obtained by Blatchford et al [10] on the ontogenesis of liver MAO in rats from var ious breeding colonies also suggested that the proportions of the two forms do not change with age. However, in contrast to the results of Mantle et al [14], these workers reported that age resulted in increased liver MAO ac tivities independently of the substrate used.…”
Section: Changes In Heart Mao Activity In Rats and Micesupporting
confidence: 50%
“…Lyles and Callingham [6] have shown that although tyramine is a good substrate for both forms of MAO it is metabolized essen tially only by MAO-A in the rat heart. Accord ing to this results, the data of Blatchford et al [10] showing an increase in heart MAO activ ity between day 5 and day 80 after birth in male Wistar rats from different breeding colo nies when tyramine is used as substrate can be interpreted as an increase in MAO-A activity. The same authors found contradictory results when 5-HT was used as substrate, with heart 5-HT-metabolizing activity decreasing steep ly between day 5 and day 40 in one of the breeding colonies studied.…”
Section: Changes In Heart Mao Activity In Rats and Micementioning
confidence: 85%